Segurando as pontas e tecendo tramas: mulheres chefes de domicílio em Minas Gerais (1770-1880) - Vanda Lucia Praxedes (2008)
This dissertation discusses issues related to female headed household, from 1770 to 1880, in Minas Gerais, Brazil. Based on various documental resources, such as wills, inventories, population maps, baptism registries and legitimating letters found in different archives in Minas Gerais, the study aimed at showing that women who were household heads distinguished themselves in society due to their experiences, family situations, social conditions, color, histories and occupations. The universe of social practices that involved female actionswas more plastic than those predicted by norms and discourses, overcoming the idea that womens roles were constrained to the private life of the homes, to household chores and to the bringing up of their children, while men were related to the public spaces, to the streets, work and social life. In practice, these roles were recreated, inverted and improvised, subverting norms and discourses, including situations in which women took charge of some traditionally male occupations. I argue that the heading of households by women was, among other elements, inherently related to the types of relationships these women established with their men, which promoted large scale changes in the valid man centered authority pattern. This work aims at de-mythfying the idea that matrifocality was limited to popular layers, especially to poor and free, emancipated or enslaved women. The phenomenon also reached white rich women, with great social prestige. It also tears down the extremely perverse dualism of Brazilian social imaginary which associates poverty to female leading, as if one is the condition for the other. It does not deny the difficulties faced by a large contingent of women who headed their households in that society. I have tried to break up with the visions that tend to reinforce stereotypes of vulnerability and poverty always related to the feminine.